El héroe nacional en contexto - Jean-Pierre Dedieu (Mélanges de la Casa de Velázquez, 2016)
By looking for heroicness in biographical dictionaries we can place the hero, not as in isolated figure but as part of a larger pantheon that includes all the memorable figures who played a part in building the nation. Only by placing the heroic figure against this backdrop can we comprehend the factors that made them soar above other historical, social and political actors past and present. This analysis highlights the coexistence of two types: a low-intensity heroicness attainable by anyone through performance of their day-to-day duties; and a high-intensity heroicness reserved for outstanding figures, which draws on the story of Christ’s sacrifice. In both cases the framework is a Christian one.